Współczesny horror rosyjski w konwencji baśniowej — na wybranych przykładach - Wilk, Anna N. (Rusycystyczne Studia Literaturoznawcze, 2016)
The article is devoted to fairytale motifs, occurring in the chosen works of contemporary Russian horror literature, such as: Новая жизнь by Aleksey Provotorov, Ей отмщение — Aykhal Mikhaylov, Sanctuary 3/9 — Anna Starobinets, Дети Робинзона Крузо — Roman Kanushkin. The main aim of the present study is to show that the witches image in the analyzed examples reveals the character that merges typical features of both the fairytales, and the horror. Therefore, the basic elements of the fairytale canon (e.g., antagonist appearance, motifs, activity, common features mainly connected with Baba Yaga or other Russian witches) have been examined in terms of their existence in the world presented.